PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL KOOPERTIF TIPE TWO STAY TWO STRAY UNTUK MELATIH KETERAMPILAN SOSIAL DAN MENUNTASKAN HASIL BELAJAR SISWA SMP - Muhammad Humaidin; Endang Susantini; Tjipto Haryono (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
Research aims to improve The development learning cooperative Model of Two Stay Two Stray type to improving Social Skills and Increase student outcomes which are validity, practically, and effectively in topic structure earth and disaster for eight grade students; and describing the realization result of instructional design plan, students learning outcomes, students responds, and the obstacles encountered in the implementation of learning. The research was conducted in two steps, The development of cooperative learning Model Two Stay Two Stray type for improve Social Skills and Increase student outcomes which referred to four-D instructional design model. The last step was tested the instructional design that has been developed on students. Subject of this research is students in class VIII SMPN 14 Bima city. Researcher use One Group Pretest-Posttest Design to test the instructional design that has been developed. Data collecting through validation, observation, test, documentation, and student respons questionnaire. Data analysis used descriptiv analysis. The development of cooperative learning Model Two Stay Two Stray type for improve Social Skills and Increase student outcome are validility, practically, and effectively topic structure earth and disaster. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran model kooperatif tipe Two Stay Two Stray yang valid, praktis, dan efektif pada pokok bahasan struktur bumi dan bencana kelas VIII; dan untuk mendeskripsikan hasil keterlaksanaan RPP, hasil belajar siswa, keterampilan sosial, respon siswa, serta Kendala-kendala yang dihadapi dalam pelaksanaan pembelajaran. Penelitian ini dilakukan dalam dua tahap, yaitu tahap pertama pengembangan perangkat pembelajaran model kooperatif Tipe Two Stay Two Stray yang mengacu pada model pengembangan four-D tetapi hanya sampai pada tahap pengembangan. Tahap kedua yaitu mengujicobakan perangkat pembelajaran yang telah dikembangkan pada siswa. Subjek penelitian ini adalah siswa kelas VIII SMPN 14 Kota Bima. Uji coba dilakukan dengan menggunakan One Group Pretest-Posttest Design. Pengumpulan data dilakukan melalui validasi, pengamatan, tes, dan angket respon siswa. Teknik analisis data menggunakan teknis analisis secara deskriptif. Hasil penelitian ini menunjukkan bahwa perangkat pembelajaran model kooperatif tipe Two Stay Two Stray  sangat valid, praktis, dan efektif untuk pokok bahasan struktur bumi dan bencana.